BUILDING THE PUBLIC ORGANIZATION BRAND BASED ON THE INTERNAL BRANDING PERSPECTIVE - Nurul Azizah; Arimurti Kriswibowo; Khusnul Khotimah; Rhea Ardhana (Jurnal Governansi, 2020)
A brand is the identity of an organization as well as the intangible asset that has significant added value for an organization. Currently, there are many organizations that are aware of the important role of brand for developing their organizations. Based on the internal branding concept, this research is aimed to gain the brand identity. The internal branding consists of three variables, namely brand orientation, brand knowledge, and brand involvement. The case was taken in Universitas Pembangunan Nasional (UPN) "Veteran" Jawa Timur (UPNVJT) that built its brand as “Bela Negara” campus since it changed its status to be a state university in 2014 and it was managed as a public organization. The samples were all employees of UPNVJT used as 267 respondents. SmartPLS software is used to test the hypothesis. The results of this research indicated that all three variables (brand orientation, brand knowledge, and brand involvement) had a positive and significant effect on brand identity. And by comparing the three variables, brand involvement had a more dominant effect on brand identity than the two other variables.